2009
DOI: 10.1016/j.jhealeco.2009.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Rising mortality and life expectancy differentials by lifetime earnings in the United States

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
50
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(53 citation statements)
references
References 30 publications
1
50
0
2
Order By: Relevance
“…Some risk factors, which themselves have effects on morbidity and mortality, could lead to overestimation of risk. 10 , 25 Roger et al 14 found that the adjusted odds ratios were reduced by 13%, 17%, and 29% for light smokers, moderate smokers, and heavy smokers, respectively, as compared with unadjusted estimates. Streppel et al 8 reported that the between-group difference in life expectancy classified by smoking status was reduced after controlling for potential confounders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some risk factors, which themselves have effects on morbidity and mortality, could lead to overestimation of risk. 10 , 25 Roger et al 14 found that the adjusted odds ratios were reduced by 13%, 17%, and 29% for light smokers, moderate smokers, and heavy smokers, respectively, as compared with unadjusted estimates. Streppel et al 8 reported that the between-group difference in life expectancy classified by smoking status was reduced after controlling for potential confounders.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, although LE and active life expectancy (ALE) have been widely used to quantify the adverse effects of smoking, 1 , 8 , 9 these descriptive measurements can lead to biased estimates for older adults—for whom various mortality and morbidity risks are present—due to the absence of adjustment for confounding variables. 10 , 11 In addition, the beneficial effects of smoking cessation remain controversial. Some studies showed that mortality risk 10 to 15 years after smoking cessation was comparable to that in never smokers 12 ; however, some researchers have argued that, from a biological perspective, the extent of the benefit depends on the reversibility of the relevant disease processes at the time of cessation.…”
Section: Introductionmentioning
confidence: 99%
“…The long-term earnings boost resulting from higher education constitutes a key mechanism linking education with retirement outcomes, such as Social Security benefit levels (Iams et al 2010), work-related pensions (Poterba et al 2007), retirement savings (Munnell and Sundén 2004; O’Rand et al 2009), and health and mortality outcomes (Cristia 2009). The observed positive association between graduate degree attainment and cumulative earnings in the 60s for men may be of particular importance.…”
Section: Discussionmentioning
confidence: 99%
“…This study finds a widening gradient for Norway, whereas no significant time change in the SES-old age mortality gradient is found for Turin. 7,8 6 See Figure 1; panel "Men 65-75" in Christia (2009). The figure suggests a convex shape; however, it does not report standard errors.…”
Section: Introductionmentioning
confidence: 99%